Going to a museum - Rissman, Rebecca (Chicago, Illinois Heinemann Library, 2012)
Explores the different types of museums, including natural history, art, science, and space museums, and what can be found at each one
Arts
a gift from book africa
1 2 13 15
Keywords: Museums -- Juvenile literature; School field trips -- Juvenile literature; School field trips